Biomimetic oxidase based on functionalized mesoporous SiO2 and metalloporphyrin for 5-hydroxymethylfurfural conversion. (November 2019) - Zou, Bin; Wang, Pengyun; Liu, Zhenjiang; Xia, Jiaojiao; Chen, baihan; Tan, Zhiyuan
Graphical abstract: Highlights: 5-Hydroxymethylfurfural(HMF) oxidation was carried out in aqueous phase. Metal porphyrin as biomimetic oxidase catalyzed HMF conversion. Excellent HMF conversion of 100% and FDCA yield of 94.94% were achieved. Abstract: 2, 5-Furandicarboxylic acid (FDCA) has the potential to replace terephthalic acid (TPA) as a building block in the preparation of bio-based and degradable polyester materials. However, the lack of efficient and stable catalysts limits the commercial viability of FDCA production. In this work, metalloporphyrins were immobilized on mesoporous SiO2 and used as a novel oxidase to convert 5-hydroxymethylfurfural (HMF) to FDCA. As the catalytic active center of P450 monooxygenases and horseradish peroxidase, supported palladium, manganese, ferri, and cobalt porphyrins via ionic-liquid-functionalized SiO2 (PdPOP-SiO2, MgPOP-SiO2, FePOP-SiO2 and CoPOP-SiO2 ) were able to simulate oxidase alone under mild conditions. 100% HMF (0.02 M) conversion and 94.94% FDCA yield were achieved using PdPOP-SiO2 as a biomimetic oxidase after a 12 h reaction at 373 K in water at atmospheric pressure. This type of mimetic oxidase is stable, inexpensive, and readily available, and the method developed in this work can potentially be used to oxidize HMF to FDCA in an industrial setting.